Hepcidin and Feritin Levels in Obese Pregnant Women and Normal Body Weight before Pregnancy - Rahma, Hadiyatur; Lumbanraja, Sarma N; Lubis, Zulfikar (Indonesian Journal of Medicine, 2018)
Background: Obesity is associated with a decrease in iron status, possibly it is an increase in hepcidin, an inflammatory protein that reduces iron absorption. Hepcidin is associated with iron homeostasis and inflammation. This study aims to determine differences in levels of hepcidin and ferritin of obesity pregnant women and normal weight before pregnancy.Subjects and Method: This was an analytic observational study with a case control design. A total of 62 pregnant women was selected by consecutive technique sampling and divided into 2 groups, namely obesity and normal weight before pregnancy. The study was conducted at RSIA BadrulAini Medan and at RSUP H.Adam Malik Medan from September to December 2016. The dependent variable of this study was the weight before pregnancy. The independent variable washepcidin levels examined by ELISA method, ferritin content with Immunochemiluminescent method. The data analysis employed Mann Whitney's different test.Results: Median of hepcidin level in obese pregnant women before pregnancy was higher than pregnant mother with normal weight of 7.08 ng / mL (2.14 to 78.18). There was no difference in hepcidin level in both groups (p = 0.578). Median ferritin levels in obese pregnant women were higher than the normal weight of 20.57 ?g / L (3.66 to 102.25). There was no difference of ferritin levels in both groups (p = 0.598).Conclusion: This study showed no difference in hepcidin levels and ferritin levels in obese pregnant women and normal weight before pregnancy.Keywords: Feritin,hepcidin, obesity before pregnancy, normal body weight before pregnancyCorrespondence: Hadiyatur Rahma. Department of Pharmacology, Faculty of Medicine, Islam Sumatera Utara University, Medan. Email: rahmahadiyatur@gmail.com.Indonesian Journal of Medicine (2018), 3(1): 22-26https://doi.org/10.26911/theijmed.2018.03.01.03